Obesity is inversely related to the risks of dental caries in Korean adults. (13th June 2017) - Song, I‐S; Han, K; Ryu, J‐J; Park, J‐B
Abstract : Objective: This study investigated whether obesity is linked with dental caries. This study hypothesized that obesity may influence the number or prevalence of dental caries in Korean adults. Subjects and Methods: Data were derived from Korea National Health and Nutrition Examination Survey performed at 2008–2010. Lifestyle, sociodemographic, and biochemical variables were analyzed. Indices related to obesity, sarcopenia, and metabolic syndrome were investigated. Finally, caries index and oral health behaviors were included for the analysis. Results: The caries index was inversely associated with increasing body mass index (BMI) and body fat quartile (all p ‐values <.01). Subjects with high waist circumference who met the inclusion criteria of metabolic syndrome were less likely to have decayed tooth ( p ‐value = .0009). Subjects with a BMI of 25 or more showed about 20% less prevalence of dental caries experience than normal individuals with a BMI of 18.5 to 23 glucose (odds ratio [95% confidence intervals] = 0.808 [0.684–0.956]). Similarly, subjects with total body fat in the highest quartile revealed about 20% less prevalence of caries experiences that those with body fat proportion in the lowest quartile (0.84 [0.672, 1.049]). Conclusions: Obesity was inversely associated with occurrence or severity of dental caries in Korean adults.